A Comparison of Determinants of Profitability of Islamic and Conventional banks - Pg Hj Sarpuddin, Dk Dewi Sarwani (2009)
This dissertation examines the profitability determinants of Conventional and Islamic banks worldwide, covering the period 2004 to 2008. It investigates whether internal bank characteristics and overall financial environment explains similarly the difference in performance of both Conventional and Islamic banks. A pooled regression model is used to see the extent to which these determinants affect profits. Generally, our analysis confirms previous findings. Size, liquidity and GDP growth was found to have significant relationship with profitability of both Conventional and Islamic banks whereas credit risk and interest rate risk have a significant negative relationship with profitability. What is surprising is that overhead appears to have contradictory relationship for Conventional and Islamic banks and that there is a negative significant relationship between performance and inflation.